Paraneoplastic exfoliative erythroderma in a cat with thymoma - KASABALIS (Δ. ΚΑΣΑΜΠΑΛΗΣ), D.; MYLONAKIS (Μ.Ε. ΜΥΛΩΝΑΚΗΣ), M. E.; PATSIKAS (Μ.Ν. ΠΑΤΣΙΚΑΣ), M. N.; PETANIDES (Θ. ΠΕΤΑΝΙΔΗΣ), T.; KOUTINAS (Α.Φ. ΚΟΥΤΙΝΑΣ), A. F. (Journal of the Hellenic Veterinary Medical Society, 2017)
A 14-year-old domestic shorthair cat was admitted with a 2-month history of excessive body weight loss and generalized exfoliative dermatitis with erythroderma. Radiographic and ultrasonographic examination revealed a cranioventral cavitary mass within the anterior mediastinum. An ultrasound-guided fine needle aspiration cytology from the mass revealed numerous small mature lymphocytes intermingled with much fewer inflammatory mast cells. These findings, along with a cellpoor interface and mixed cell dermatitis demonstrated on skin histopathology, made the diagnosis of paraneoplastic exfoliative dermatitis straightforward. This uncommon case illustrates the relative value of keratosebborheic skin disease as a useful indicator of an internal malignancy in the cat.